How Direct-to-Consumer Brands Can Continue to Grow: They need to revise the marketing innovations that gave them early momentum - Rangan, Kasturi; Higgins, Matt; Schlesinge, Leonard; Corsten, Daniel (Harvard Business Review, 2021)
Direct-to-consumer (DTC) brands such as Allbirds, Casper, Peloton, and Warby Parker have creatively found a weakness in the marketing citadel of incumbent brands. By using data gleaned from daily interactions with customers, these brands have been able to adapt how they serve their unique customer communities across a start-to-finish purchase journey. The best of them have parlayed that ability into a profitable business model applied across multiple channels and customer segments. But as successful DTC brands mature, they must recognize the need to evolve. The authors offer four principles for continued success: (1) Focus on deepening customer relationships, not just making comparisons with competitors. (2) Accompany the customer beyond the initial transaction. (3) Omnichannel is about value addition, not cost reduction. (4) Strengthen the core first; consider extensions later.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura